THE INFLUENCE OF PRIVACY, SECURITY AND TRUST ANALYSIS ON ONLINE PURCHASE DECISIONS AT BLIBLI (CASE STUDY ON UNIVERSITY STUDENTS DEVELOPMENT OF PANCA BUDI MEDAN) - Afriyanti, Annisa; Saragih, Megasari Gusandra (Universitas Negeri Medan, 2024)
This research was conducted on Friday Saturday Class Students of the Management Study Program of Panca Budi Medan Development University. The purpose of the study was to find out how privacy, security and trust affect the online purchase decision of the BliBli application. The population in this study was 431 respondents and used the Slovin technique so that the sample was determined to be 81 respondents. This study used a descriptive method with a quantitative approach which was processed with the SPSS version 25 application with a multiple linear regression analysis model. The data source used primary data taken directly from respondents. The results showed that partial privacy had a positive and significant effect on purchasing decisions. Security has a positive and significant influence on purchasing decisions. Trust has a positive but not significant effect on purchasing decisions. While simultaneously the variables of privacy, security and trust have a positive and significant effect on purchasing decisions. The contribution of the influence of the independent variable was 42.3% and the rest was influenced by other variables that were not studied in this study.